Adaptive immune response to BNT162b2 mRNA vaccine in immunocompromised adolescent patients - Bader, Guy; Itan, Michal; Edry-Botzer, Liat; Cohen, Hadar; Haskin, Orly; Mozer-Glassberg, Yael; Harel, Liora; Munitz, Ariel; Mandelblit, Nufar Marcus; Gerlic, Motti (Frontiers in Immunology, 2023)
Protective immunity against COVID-19 is orchestrated by an intricate network of innate and adaptive anti-viral immune responses. Several vaccines have been rapidly developed to combat the destructive effects of COVID-19, which initiate an immunological cascade that results in the generation of neutralizing antibodies and effector T cells towards the SARS-CoV-2 spike protein. Developing optimal vaccine-induced anti-SARS- CoV-2 protective immunity depends on a fully competent immune response. Some evidence was gathered on the effects of vaccination outcomes in immunocompromised adult individuals. Nonetheless, protective immunity elicited by the Pfizer Biontech BNT162b2 vaccine in immunocompromised adolescents received less attention and was mainly focused on the antibody response and their neutralization potential. The overall immune response, including T-cell activities, was largely understudied. In this study, we characterized the immune response of vaccinated immunocompromised adolescents. We found that immunocompromised adolescents, which may fail to elicit a humoral response and develop antibodies, may still develop cellular T-cell immunity towards SARS-CoV-2 infections. Furthermore, most immunocompromised adolescents due to genetic disorders or drugs (Kidney and liver transplantation) still develop either humoral, cellular or both arms of immunity towards SARS-CoV-2 infections. We also demonstrate that most patients could mount a cellular or humoral response even after six months post 2nd vaccination. The findings that adolescents immunocompromised patients respond to some extent to vaccination are promising. Finally, they question the necessity for additional vaccination boosting regimens for this population who are not at high risk for severe disease, without further testing of their post-vaccination immune status.